2021
DOI: 10.1007/s11033-021-06528-1
|View full text |Cite
|
Sign up to set email alerts
|

Atiprimod triggered apoptotic cell death via acting on PERK/eIF2α/ATF4/CHOP and STAT3/NF-ΚB axis in MDA-MB-231 and MDA-MB-468 breast cancer cells

Abstract: Purpose: The constitutive activation of STAT3 through receptor tyrosine kinases triggered breast cancer cell growth, and invasion-metastasis. Atiprimod impacts anti-proliferative, anti-carcinogenic effects in hepatocellular carcinoma, lymphoma, multiple myeloma via hindering the biological activity of STAT3. Dose-dependent atiprimod evokes rst autophagy as a survival mechanism and then apoptosis due to prolonged ER stress in pituitary adenoma cells. The therapeutic e ciency and mechanistic action of atiprimod … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 39 publications
(64 reference statements)
1
3
0
Order By: Relevance
“…It is reported that Nox4 facilitates autophagy and osteoclastogenesis by the activation of the PERK/EIF2α/ATF4 signaling [29]. Atiprimod-induced ERS-mediated autophagy through regulating the PERK/EIF2α/ATF4/CHOP axis in breast cancer [30]. In this study, we found that IPO7 depletion markedly suppressed the EIF2AK3, ATF4, CHOP, and p-EIF2α levels.…”
Section: Discussionsupporting
confidence: 54%
“…It is reported that Nox4 facilitates autophagy and osteoclastogenesis by the activation of the PERK/EIF2α/ATF4 signaling [29]. Atiprimod-induced ERS-mediated autophagy through regulating the PERK/EIF2α/ATF4/CHOP axis in breast cancer [30]. In this study, we found that IPO7 depletion markedly suppressed the EIF2AK3, ATF4, CHOP, and p-EIF2α levels.…”
Section: Discussionsupporting
confidence: 54%
“…In parallel, the unfolded protein response (UPR) is also activated in reply to ER stress. Although the UPR might help reduce the load of unfolded proteins to maintain cell survival ( Marciniak et al, 2022 ), persistent UPR caused by long-term severe ER stress could induce apoptosis through protein kinase R-like endoplasmic reticulum kinase (PERK)/eukaryotic translation initiation factor 2α (eIF2α)/activating transcription factor 4 (ATF4)/CCAAT enhance-binding protein homologous protein (CHOP) pathway ( Hetz, 2012 ; Yu et al, 2021b ; Coker-Gurkan et al, 2021 ). As a transcription factor, CHOP promotes mitochondrial dependent apoptosis by upregulating the expression of pro-apoptotic proteins comprise BAX, BAK and BIM.…”
Section: Different Outcomes Of Calcium Overload-based Ion Interferenc...mentioning
confidence: 99%
“…We then examined the effects of TBZPy-PDT on ER stress, which is a cellular response to various stimuli that disrupt ER homeostasis and cause accumulation of unfolded or misfolded proteins in the ER lumen (Grebenová et al, 2003). ER stress activates three major signaling pathways: PERK/eIF2α, IRE1/XBP1, and ATF6 (Coker-Gurkan et al, 2021;Walter and Ron, 2011). Among them, PERK/eIF2α is considered to be the main pathway involved in PDT-induced apoptosis (Chen et al, 2019).…”
Section: Tbzpy-pdt Triggered Ers Via the Perk/eif2α Signaling Pathwaymentioning
confidence: 99%